2016
DOI: 10.3390/machines4020012
|View full text |Cite
|
Sign up to set email alerts
|

Z-Damper: A New Paradigm for Attenuation of Vibrations

Abstract: Abstract:Magnetic linear gear provides a new and unique opportunity for coupling mechanical impedances and optimizing vibration damping. In the present paper a new magneto-mechanical vibration damper (the so-called Z-damper) is described. Its expected theoretical dynamic behavior shows a particularly high damping capability, a low frequency, as well as an optimal behavior for high frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Linear magnetic gears are devices able to amplify the displacement of any oscillating mechanical element [10]. As they are the linear version of rotational magnetic gear [11] they are also expected to inherit their interesting properties like not needing lubrication, zero backlash, large temperature range, and long working life [12].…”
Section: Physics Of the -Transmittermentioning
confidence: 99%
See 1 more Smart Citation
“…Linear magnetic gears are devices able to amplify the displacement of any oscillating mechanical element [10]. As they are the linear version of rotational magnetic gear [11] they are also expected to inherit their interesting properties like not needing lubrication, zero backlash, large temperature range, and long working life [12].…”
Section: Physics Of the -Transmittermentioning
confidence: 99%
“…Some of us [10] suggested that linear magnetic gears can provide mechanical impedance matching of a vibration control device, that is, a damper, an active actuator, or a tuned vibration absorber, and be used to multiply its effect in the same way that electrical transformers are used in electrical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to anticipate the major step forward that contactless technology can bring to common industrial applications. For instance, one of the most important breakthroughs would be the reduction of noise and vibration in aerospace applications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the controllable and varied physical properties of smart materials, they are also used for living infrastructures, mechanical structures, and seismic vibration controls for decades . Smart materials and structures that possess electromechanical characteristics have been widely used for active vibration control or semi-active vibration control, such as piezoelectric damper [4][5][6][7][8], eddy current damper [9], magnetostrictive spring [10], magneto-rheological fluid (MRF) damper [11][12][13], electro-rheological fluid (ERF) damper [14][15][16][17], shape memory alloy (SMA) [18][19][20][21], and electromagnetic and piezoelectric shunt damper [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Smart materials have one or more properties changed by the external stimuli, such as temperature, stress, electric field or magnetic field.…”
Section: Introductionmentioning
confidence: 99%